Cuidados paliativos pediátricos: atributos para uma rede de cuidado integral - Menegussi, Juliana Morais (Universidade Federal de São Carlos, 2026)
Palliative care is understood as an approach that aims to improve the quality of life of adults and children, as well as their families, who face problems associated with health conditions that may limit or threaten the continuity of life. This approach seeks to prevent and alleviate suffering, whether physical, psychological, social, or spiritual in nature. This research is motivated and justified by the need to advance the current state of the pediatric palliative care approach, from the perspective of comprehensive and networked care. For that, action research was carried out as a methodological approach, anchored in the theoretical perspective of comprehensiveness. Six meetings were held with family members and palliative care professionals with the main objective of collectively building attributes for a pediatric palliative care network, from the perspective of comprehensiveness. The results highlight seven attributes to be considered in pediatric palliative care: child- and family-centered care, total pain management as the structuring axis of care, humanized health practices, guaranteed resources and access to technologies, networked care, integration among different policies and community networks, and qualification and support for healthcare work. The identified attributes reveal that a comprehensive pediatric palliative care network could be built through the articulation between lived suffering, ethical care practices, network organization, and political commitment, shaping a goal that transforms laws into lived rights and care into collective responsibility. May this research serve as an invitation to continue the debate, research, and political action in pediatric palliative care in our country.
Pediatric palliative care: attributes for a comprehensive care network
Keywords: Cuidados paliativos; Pediatria; Integralidade; Condição crônica e complexa de saúde; CIENCIAS DA SAUDE::SAUDE COLETIVA; 3. Saúde e Bem-Estar